Manajemen Ekstrakulikuler Rohis di Sekolah Menengah Atas (SMA) Palembang - Asri Arumsari; Muh Misdar; Yulia Tri Samiha (Studia Manageria, 2020)
The background in this research is to study how to manage the spiritist extracurricular in high schools (SMA) in Palembang's flagship schools including SMAN 1, SMAN 5, and SMAN 17 Palembang. Rohis extracurricular management is very necessary so that the purpose of this extracurricular can be done easily.The formulation of the problem in this study is how the management of spiritual extracurricular which includes planning, organizing, implementing and controlling in SMAN 1, SMAN 5, and SMAN 17 Palembang. The type of research used in the study of Rohis Religious Management Program in Palembang's High School is qualitative research. The research instrument uses documentation, interviews, observation and triangulation. And data analysis uses reduction, data presentation and data verification.The results showed that the management of the religious program in the top high schools in Palembang, the three schools planned at the beginning of the new school year each year to determine what activities would be carried out. Organizing, all mentoring members and coaches always work together to help each other in mentoring activities. Implementation, mentoring activities carried out outside the teaching and learning activities of students. Supervision, of the three schools the supervisor does not supervise regularly and the time is uncertain, whenever the supervisor can supervise